2008
DOI: 10.1093/aob/mcn165
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Requirements for Seed Germination and Seedling Development Determine Timing of Seedling Emergence of Three Monocotyledonous Temperate Forest Spring Geophytes

Abstract: A continuous development of the embryo and seedlings of the three species was observed from the moment the seeds were dispersed until seedlings emerged. A sequence of high summer temperatures followed by decreasing autumn and winter temperatures was required for all developmental processes to be completed. Although a time lag occurs between radicle protrusion and seedling emergence, the term 'epicotyl dormancy' does not apply here, due to the absence of a period of developmental arrest. Timing of first seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 30 publications
9
76
0
1
Order By: Relevance
“…The results obtained in the germination trials were consistent with these data, because in these experiments it was shown that for temperatures higher than 10°C the final germination percentages were very high for cypselas from all the populations studied. In addition, cypselas readily germinated in all the temperatures tested (except 10°C), as similarly reported for many temperate climate species around the world (Baskin and Baskin, 1998;Vandelook and Van Assche, 2008). Since mountain ecosystems are typically subjected to a short growing season, this strategy could be claimed to ensure enough time for seedling establishment (Chambers et al, 1987;Korner, 1999;Grime, 2001).…”
Section: Discussionsupporting
confidence: 64%
“…The results obtained in the germination trials were consistent with these data, because in these experiments it was shown that for temperatures higher than 10°C the final germination percentages were very high for cypselas from all the populations studied. In addition, cypselas readily germinated in all the temperatures tested (except 10°C), as similarly reported for many temperate climate species around the world (Baskin and Baskin, 1998;Vandelook and Van Assche, 2008). Since mountain ecosystems are typically subjected to a short growing season, this strategy could be claimed to ensure enough time for seedling establishment (Chambers et al, 1987;Korner, 1999;Grime, 2001).…”
Section: Discussionsupporting
confidence: 64%
“…The sites where G. lútea grows maintain high soil moisture content throughout the year. Therefore, once the gentian seeds have lost their dormancy, they will germinate in a wide range of temperatures, as similarly reported for many températe climates species around the world (Baskin and Baskin 1998;Vandelook and Van Assche 2008). Since mountain ecosystems are typically subjected to a short growing season, this strategy could be claimed to ensure enough time for seedling establishment (Grime 2001;Kórner 2003).…”
Section: Discussionmentioning
confidence: 79%
“…In N. pseudonarcissus (Vandelook & Van Assche, 2008), N. eugeniae (Copete et al, 2014) and N. hispanicus (Copete et al, 2011), growth of the embryo is continuous throughout summer, radicle emergence occurs in early autumn and shoot emergence is delayed up to late winter-early spring, so corresponding to deep simple epicotyl MPD pattern. In N. alcaracensis (Herranz et al, 2013b), dormancy break and embryo growth require only cold stratification and seeds have intermediate complex MPD, while in N. longispathus (Herranz et al, 2013a) dormancy break, embryo growth and radicle emergence require warm stratification followed by cold one, corresponding to non-deep complex MPD pattern (Baskin & Baskin, 1998).…”
Section: Plant Materials and Seed Sourcementioning
confidence: 99%
“…The critical embryo length for radicle emergence is the length of the embryo at the time the seed coat splits but before the radicle emerges (Vandelook & Van Assche, 2008). In N. radinganorum, the critical embryo length for radicle emergence was 2.62 mm (s.e.=0.04 mm, n=20, range=2.20-3 mm).…”
Section: Phenology Of Embryo Growth and Of Radicle And Shoot Emergencementioning
confidence: 99%